Optimalisasi Kuliah Perdana Dalam Upaya Pencegahan Perundungan Di Pendidikan Tinggi - Litya Surisdani A; Hesti Ayu Wahyuni (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Bullying in the Higher Education environment, also known as campus, has become an increasingly pressing issue in recent years. This phenomenon not only includes verbal and physical bullying but also reaches the digital dimension through cyberbullying. Students who are victims of bullying face a range of serious harms, including negative impacts on their emotional and mental well-being. These impacts can include increased levels of stress, anxiety and depression, which in turn can impair their academic performance and threaten long-term psychological health. In addition, bullying can also lead to significant social isolation and even jeopardise the physical safety of the victim in certain cases. The importance of creating a safe, supportive, and inclusive campus environment is crucial in effectively and preventively addressing this bullying issue. This socialisation was held in the inaugural lecture at Stifera Semarang online. Overall, the inaugural lecture on anti-bullying prevention is an important first step in shaping mindsets and practices that support a campus culture free from bullying. The inaugural lecture can be a platform to build a safe campus culture, where every member of the community is prepared to recognise, report, and prevent bullying.